Ratiometric delivery of two therapeutic candidates with inherently dissimilar physicochemical property through pH-sensitive core–shell nanoparticles targeting the heterogeneous tumor cells of glioma - He-Lin Xu; Zi-Liang Fan; De-Li ZhuGe; Meng-Qi Tong; Bi-Xin Shen; Meng-Ting Lin; Qun-Yan Zhu; Bing-Hui Jin; Yasin Sohawon; Qing Yao; Ying-Zheng Zhao (Drug Delivery, 2018)
Currently, combination drug therapy is one of the most effective approaches to glioma treatment. However, due to the inherent dissimilar pharmacokinetics of individual drugs and blood brain barriers, it was difficult for the concomitant drugs to simultaneously be delivered to glioma in an optimal dose ratio manner. Herein, a cationic micellar core (Cur-M) was first prepared from d-α-tocopherol-grafted-ε-polylysine polymer to encapsulate the hydrophobic curcumin, followed by dopamine-modified-poly-γ-glutamic acid polymer further deposited on its surface as a anion shell through pH-sensitive linkage to encapsulate the hydrophilic doxorubicin (DOX) hydrochloride. By controlling the combinational Cur/DOX molar ratio at 3:1, a pH-sensitive core–shell nanoparticle (PDCP-NP) was constructed to simultaneously target the cancer stem cells (CSCs) and the differentiated tumor cells. PDCP-NP exhibited a dynamic diameter of 160.8 nm and a zeta-potential of –30.5 mV, while its core–shell structure was further confirmed by XPS and TEM. The ratiometric delivery capability of PDCP-NP was confirmed by in vitro and in vivo studies, in comparison with the cocktail Cur/DOX solution. Meanwhile, the percentage of CSCs in tumors was significantly decreased from 4.16% to 0.95% after treatment with PDCP-NP. Overall, PDCP-NP may be a promising carrier for the combination therapy with drug candidates having dissimilar physicochemical properties.